PENGARUH KUALITAS LAYANAN JASA EKSPOR IMPOR TERHADAP KEPUASAN PELANGGAN DI KANTOR DIREKTORAT JENDERAL BEA DAN CUKAI SURABAYA - Toa, Yohanes Paulus; Pujianto, Agung; Tjahjono, Endro (Jurnal Dinamika Administrasi Bisnis, 2015)
Â This research is quantitative research. The independent variable used in this study is the reliability, responsiveness, and assurance, while the dependent variable is customer satisfaction Customs Surabaya. Analysis of the data used is multiple linear regression, F test, t test, and the coefficient of determination.The results showed that the Reliability (X1), Responsiveness (X2) and Assurance (X3) significantly affects customer satisfaction. Beta value indicates that the variable Assurance (X3) has the greatest value, namely 0.433., It was concluded that the variables mempuyai the most impact on customer satisfaction with the services DGCE is variable Assurance (X3). The coefficient of determination R2 obtained for 0.595, meaning variation (fluctuation) of customer satisfaction terhada service DJBC Surabaya (Y), able to be explained by changes in variable Reliability (X1), Responsiveness (X2) and Assurance (X3), together 59.5%, while the remainder is equal to 40.5% is influenced by other variables not examinedKeywords: Customer satisfaction, reliability, responsiveness, and assurance